Comparative evaluation of dentinal defects induced by hand files, hyflex, protaper next and one shape during canal preparation: A stereomicroscopic study - Ekta Garg; Shafia Sarfi; Dildeep Bali; Akhil K Garg (Wolters Kluwer Medknow Publications, 2017)
Aim: This study aims to evaluate and compare the incidence of dentinal defects induced by Hand Files, HyFlex CM, ProTaper Next (PTN), and One Shape during canal preparation. Materials and Methods: One hundred and fifty extracted mandibular premolar teeth with single root canal were selected. Specimens were then divided into five groups with thirty specimens each. Group I: Specimens were prepared with hand instruments. Group II: Specimens were prepared with HyFlex CM rotary files (Coltene) using a crown-down technique according to the manufacturer's instructions. Group III: Specimens were prepared with PTN rotary files (Dentsply) using a crown-down technique according to the manufacturer's instructions. Group IV: Specimens were prepared with One Shape Single file rotary system (MicroMega) using a crown-down technique according to the manufacturer's instructions. Group V: Specimens were used as a control and left unprepared. All roots were cut horizontally at 3, 6, and 9 mm from the apex. Sections were then viewed under stereomicroscope and dentinal defects were registered as "no defect," "fracture," and "other defects." Statistical Analysis: Results of the study were subjected to Chi-square test. Results: Results were expressed as the number and percentage of defected, partially defected and roots with no defects in each groups. Conclusion: Hand files and One Shape file system caused less root defects compared to PTN and HyFlex file systems.